2018
DOI: 10.1080/02699052.2018.1531303
|View full text |Cite
|
Sign up to set email alerts
|

Participation after traumatic brain injury: the surplus value of social cognition tests beyond measures for executive functioning and dysexecutive behavior in a statistical prediction model

Abstract: Objective: This study evaluates the contribution of measures for social cognition (SC), executive functioning (EF) and dysexecutive behavior to the statistical prediction of social and vocational participation in patients with traumatic brain injury (TBI), taking into account age and injury severity. Method: A total of 63 patients with moderate to severe TBI participated. They were administered a semistructured Role Resumption List for social (RRL-SR) and vocational participation (RRL-RTW). EF was measured wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
(89 reference statements)
0
11
1
1
Order By: Relevance
“…Contrary to our hypothesis, we found that theory of mind (ToM), empathy, emotion recognition and behavioural control were not associated with restrictions in participation three to four years after stroke. This is inconsistent with the reported relationship between emotion perception and participation in stroke in a previous study (Cooper et al, 2014) and with the literature on the relationship between social cognition and participation in moderate to severe TBI (May et al, 2017;Ubukata et al, 2014;Westerhof-Evers et al, 2018). Several factors may contribute to these contradictory findings.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations
“…Contrary to our hypothesis, we found that theory of mind (ToM), empathy, emotion recognition and behavioural control were not associated with restrictions in participation three to four years after stroke. This is inconsistent with the reported relationship between emotion perception and participation in stroke in a previous study (Cooper et al, 2014) and with the literature on the relationship between social cognition and participation in moderate to severe TBI (May et al, 2017;Ubukata et al, 2014;Westerhof-Evers et al, 2018). Several factors may contribute to these contradictory findings.…”
Section: Discussioncontrasting
confidence: 79%
“…Social cognitive deficits were mild as well; even though patients scored significantly lower compared to controls on emotion recognition, ToM and behavioural control, effect sizes were only small (Nijsse et al, 2019b) and a maximum of only 4.2% of the patients were impaired to a degree of two standard deviations or more below control mean. Support for the role of stroke severity in the relationship of social cognition and participation is found in the fact that social cognition does not predict community participation in healthy controls (Pijnenborg et al, 2009) and that studies reporting a relationship in TBI patients involved participants with moderate to severe TBI (Knox & Douglas, 2009;May et al, 2017;Struchen et al, 2008;Ubukata et al, 2014;Westerhof-Evers et al, 2018). Taken together, our results indicate that with mild stroke severity, social cognitive impairments and participation limitations are only mild and not associated.…”
Section: Bivariate Analysesmentioning
confidence: 49%
See 2 more Smart Citations
“…However, less is known about whether these individuals eventually participate in social and productive activities. In fact, many studies of participation after TBI exclude persons with the most severe impairments and lower levels of function for logistical reasons (e.g., inability to complete self-report questionnaires or primary residence in a non-community setting) (7,8). Alternatively, patients with severe TBI and prolonged impairments may be grouped with less severe patient populations (e.g., moderate TBI) (9), thus potentially masking cohort-specific effects (10,11).…”
Section: Introductionmentioning
confidence: 99%